THE IMPLEMENTATION OF KANG PISMAN PROGRAM IN IMPROVING STUDENTS’ ECOLOGICAL INTELLIGENCE (A Descriptive Study of Ecological Intelligence of Students in Bandung State Middle School 10) - Rosalina, Anindya (International Journal Pedagogy of Social Studies, 2019)
This study was structured to find out the improvement of the ecological intelligence of students in SMP Negeri 10 Bandung after the implementation of the Kang Pisman program. In the school environment, the problem of rubbish becomes difficult to overcome because students who use plastic for daily snacks still dominate, even though trash bins are provided, not a few of them still throw garbage in their place, which then becomes one of the causes of discomfort on the school environment where they study. The researcherswere interested to find out Kang Pisman implementation process and its influence on students. The method used in this research was descriptive qualitative with data collection techniques through observation and interviews. The subjects in this study were divided into 3 categories namely the coach of the Kang Pisman program, students who were members of Kang Pisman, and students who were not members of Kang Pisman. The results of observations and interviews show that the students' ecological intelligence program has increased significantlyafter the implementation of Kang Pisman program so far, as seen from the habits of students to separate the increased waste, also in reducing waste where students are accustomed to bringing tumblers or lunch boxes to school, and to utilize garbage in general, students have participated in the effort even though they have not directly contributed to their activities, namely visiting the garbage bank and making regular work. Besides, investigated from several schools that the researchers observed, the implementation of Kang Pisman in SMP Negeri 10 Bandung was carried out well. This study concluded that Kang Pisman program implementation improves the students’ ecological intelligence, although in some aspects ,students who are members of Kang Pisman experienced an increase in ecological intelligence more than non-members of Kang Pisman because of the variety of activities carried out more than students who are not members of Kang Pisman.